Membangun Sistem Smart Trash Menggunakan Mikrokontroler Motor Servo Panjerino - Hirmawan, Yuda; Riyanto, Eko; Solikhin, Solikhin (Universitas PGRI Semarang, 2023)
To cultivate good behavior and care for the environment, SD Negeri 2 KuwasenJepara promotes proper waste disposal, but in reality, there are still many students who don't do it. The purpose of this research is to build a smart trash can to socialize waste disposal in an attractive way for students. We use a manual trash can that is integrated with the Arduino Uno. This smart trash system is able to open automatically when it detects movement within 50 cm and vice versa, and can emit a